An Efficient Synthesis of Optically Pure Nδ-Monomethylated l-Arginine and l-Ornithine - Litty, Felix-A.; Girreser, Ulrich; Clement, Bernd; Schade, Dennis (Synthesis, 2016)
Nω-Methylated l-arginines such as asymmetric dimethyl-l-arginine (ADMA) and monomethyl-l-arginine (NMMA) are well-known endogenous modulators of the nitric oxide (NO) generating system. To understand the (patho)physiological role and impact of Nδ-methylation of l-arginine and l-ornithine an efficient synthesis of the pure enantiomers was needed. A synthetic approach that furnished both the desired amino acids in 8–10 steps from commercially available N-Boc-l-ornithine in good overall yields (20–21%) and with high optical purity (>99% ee) is reported.
Keywords: alkylation; amino acids; bioorganic chemistry; chiral pool; chiral resolution; protecting groups